Legal tender - Dror Goldberg (Bar-Ilan University, Department of Economics, 2009)
The legal foundation of the monetary system is the law of legal tender. The 'legal tender' concept is used in models to describe almost anything except for what it really means in actual laws. Such errors prevent an accurate evaluation of the importance of this legal status. This note explains in simple terms what 'legal tender' really means.
Keywords: E42; K12; 330; Legal tender; Contract law; Taxes; Währungssystem; Vertragsrecht